2011
DOI: 10.1016/j.ijrobp.2009.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Breast Tumor Relapse: Local Recurrence Versus New Primary Tumor and the Effect of Whole-Breast Radiotherapy on the Rate of New Primaries

Abstract: Purpose: The justification for partial breast radiotherapy after breast conservation surgery assumes that ipsilateral breast tumor relapses (IBTR) outside the index quadrant are mostly new primary (NP) tumors that develop despite radiotherapy. We tested the hypothesis that whole-breast radiotherapy (WBRT) is ineffective in preventing NP by comparing development rates in irradiated and contralateral breasts after tumor excision and WBRT. Methods and Materials: We retrospectively reviewed 1,410 women with breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 32 publications
5
24
0
3
Order By: Relevance
“…In a large retrospective study on 1,410 patients, Gujral et al [24] reported a cumulative incidence rate of new primaries after whole-breast irradiation at 5, 10, and 15 years of 0.8%, 2%, and 3.5%, respectively. The authors concluded that whole-breast irradiation approximately halves the rate of new primaries.…”
Section: Therapy Of Ipsilateral Breast Tumor Recurrencementioning
confidence: 99%
“…In a large retrospective study on 1,410 patients, Gujral et al [24] reported a cumulative incidence rate of new primaries after whole-breast irradiation at 5, 10, and 15 years of 0.8%, 2%, and 3.5%, respectively. The authors concluded that whole-breast irradiation approximately halves the rate of new primaries.…”
Section: Therapy Of Ipsilateral Breast Tumor Recurrencementioning
confidence: 99%
“…Undoubtedly, tumor recurrence occurs in the original tumor bed in the early follow-up period, while, the long-term tumor recurrences tend to be more distant from the primary area. In the IORT technique findings such as redness, warmth, and hyper-pigmentation can be seen at the irradiation field (49,50).…”
Section: Side Effects Of the Iort Techniquementioning
confidence: 99%
“…Les deux facteurs le plus souvent pris en compte sont la localisation de la récidive par rapport à la première tumeur et le type histologique (c'est-à-dire canalaire, lobulaire, tubuleux… mais non in situ versus invasif) [37,48,58,71,89,110]. La différence entre vraie récidive et nouveau cancer repose actuellement sur des critères mal défi nis, non standardisés.…”
Section: Dossierunclassified